Asymmetric Biphasic Hydrophobic/Hydrophilic Poly(Lactic Acid)–Polyvinyl Alcohol Meshes with Moisture Control and Noncytotoxic Effects for Wound Dressing Applications - Cerda-Villablanca, E (John Wiley and Sons Inc, 2019)
A noncytotoxic film was developed in this work with asymmetric biphasic properties (hydrophilic/hydrophobic) that allow for gas exchange. Among its many biomedical applications, it could be applied as a wound dressing material where the absorption of exuded fluids and control of water loss is required simultaneously. Thin meshes were developed modifying one face of poly(lactic acid) (PLA) electrospun mats with polyvinyl alcohol (PVA) using a simple photografting methodology. The contact angle of the modified face of the film was 44 while that of the other face was the original value of 122. The chemical modification was covalent, as confirmed by X-ray photoelectron spectroscopy, stable over time and resistant to successive washing steps. Cytotoxic assays with fibroblast cells showed that PVA photo-grafted onto PLA meshes present a high cell viability percentage. © 2019 Wiley Periodicals, Inc.